PENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA MELALUI PENERAPAN LEMBAR KERJA SISWA BERBASIS PENEMUAN - Khoiriah Khoiriah (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The research objective is to describe the application of discovery-based student worksheets to the Human Circulatory System Basic Competence to improve science process skills and learning outcomes. This research is a classroom action research recruiting students in class VIII-5 at SMP Negeri 32 Bandar Lampung school year 2018/2019 through purposive sampling technique. The research instrument is a learning device and research data collector. Data collection on science process skills is carried out using an observation instrument of science process skills while learning outcomes data use written test instruments. The data were analyzed qualitatively and quantitatively. The data analysis results show the students’ average percentage of science process skills in the first cycle of 40.11% lies in the medium category, the second cycle of 67.19% in the high criteria, while the third cycle of 86.46% was very high. The average students’ competency in the first cycle showed 69.44 lies in a high category, the second cycle 70.95 is also high category and 76.56 competencies in the third cycle with very high criteria. Thus the application of student worksheets based on this invention has met the criteria of success indicators and they have improved science process skills and learning outcomes of the students in class VIII-5 in SMP Negeri 32 Bandar Lampung in the academic year 2018/2019.